Development of digital energy meter for domestic appliances - Mohd Razaqi, Zamri (2009)
An energy meter is a device that able to measure electric energy at any one time. The energy data is very important for the study about energy demand especially in residential sector. The meters that can be found in the market nowadays are expensive because they work on operation principle that requires the use of expensive hardware. Hence, a digital meter that can measure electrical energy consumed by domestic appliances such as kettle, television, toaster, and others has been developed. This meter is robust, user friendly and informative enough for the purpose of simple data gathering. The project involved of hardware designing and microcontroller interfacing. In hardware design, the energy will be determined in digital form. The function of the microcontroller is for the output part. It consists of soft code specially written to calculate energy cost and to convert digital energy signals to binary code decimal. The total energy consumption used by the appliances and the related cost are given as seven segment display after decoding.